2017
DOI: 10.1177/0144598717716282
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of potential energy and matter production from biomass pyrolysis with artificial neural network

Abstract: The potentiality determination of renewable energy resources is very important. The biomass is one of the alternative energy and material resources. There is great effort in their conversion to precious material but yet there is no generalized rule. Therefore, the prediction of the energy and material potentials of these resources has gained great importance. Also, the solution to environmental problems in real time can be found easily by predicting models. Here, the basic products of pyrolysis process, char, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 27 publications
1
16
1
2
Order By: Relevance
“…Still, ANN may not be suitable for novel technologies like biomass pyrolysis or gasification where the amount of experimental data is limited. For the easy approximation of the pyrolysis or gasification data, a feed-forward network (FFN) and cascade-forward network (CFN) can be useful in predicting the relationship between multivariant, nonlinear biomass, and product yields. …”
Section: Modeling Approaches To the Pyrolysis Processmentioning
confidence: 99%
“…Still, ANN may not be suitable for novel technologies like biomass pyrolysis or gasification where the amount of experimental data is limited. For the easy approximation of the pyrolysis or gasification data, a feed-forward network (FFN) and cascade-forward network (CFN) can be useful in predicting the relationship between multivariant, nonlinear biomass, and product yields. …”
Section: Modeling Approaches To the Pyrolysis Processmentioning
confidence: 99%
“…Such studies differ drastically in experimental systems ( Tithonia diversifolia weed biomass [ 63 ], low-density polyethylene [ 64 ], high-density polyethylene [ 68 ], safflower seed press cake [ 65 ], durian rinds [ 69 ], rape straw [ 70 ], coal gangue and peanut shell [ 71 ], pet coke [ 72 ], sewage sludge and peanut shell [ 73 ], sewage sludge and coffee grounds [ 74 ], vegetable fibers [ 75 ], rice husk and sewage sludge [ 45 ], sludge, watermelon rind, corncob, and eucalyptus [ 76 ], Sargassum sp. seaweed [ 77 ], cotton cocoon shell, tea waste, and olive husk [ 66 ], mechanoactivated coals [ 78 ], cattle manure [ 79 ], lignocellulosic forest residue and olive oil residue [ 80 ], cotton cocoon shell, fabricated tea waste, olive husk, and hazelnut shell [ 81 ]) and in some minor details, but the general concept remains the same. Thus, we illustrate it with the study by Kataki et al [ 63 ], who used a neural network model (4-14-1) to predict the product yield for the pyrolysis of dried weed biomass.…”
Section: Prediction Of Conversion Data (Single Value Whole Curve)mentioning
confidence: 99%
“…Table 1a and Table 1b present the literature contributions in this field. The use of wood waste [15,[23][24][25][26] and agricultural residues [16,17,27,28] as feedstock are common in the literature due to its low market value and availability [29,30]. The related variables with output can be used to reach more accurate results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Merdun and Sezgin [24] reported that the models in more homogeneous characteristics (single or a few biomass types) and more related inputs with output may result in better performances. Aydinli et al [27] specified that in order to attain the more reliable models, the variables such as particle size and residence time as well as the ultimate analysis data can be considered as input parameters. The yields and composition of the products depend on the pyrolysis conditions, properties of biomass, and pyrolysis method.…”
Section: Literature Reviewmentioning
confidence: 99%